2021
DOI: 10.1177/03611981211023766
|View full text |Cite
|
Sign up to set email alerts
|

Using Artificial Intelligence to Estimate Nonlinear Resilient Modulus Parameters from Common Index Properties

Abstract: The Mechanistic–Empirical Pavement Design Guide (MEPDG) considers a hierarchical approach to determine the input values necessary for most design parameters. Level 1 requires site-specific measurement of the material properties from laboratory testing, whereas other levels make use of equations developed from regression models to estimate the material properties. Resilient modulus is a mechanical property that characterizes the unbound and subgrade materials under loading that is essential for the mechanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…63,64 In recent years, machine learning and artificial intelligence techniques (hereinafter termed AI techniques) have gained popularity in geotechnical engineering applications [65][66][67] to lower costs and increase efficiency. 68,69 AI technology has been successfully applied for the estimation of the mechanical properties of saturated soils (e.g., the non-linear resilient modulus and shear strength parameters) [70][71][72][73][74] and the stability analysis of geo-structures (e.g., slopes, retaining walls, and embankments). [75][76][77] Many studies have demonstrated that AI techniques can be used as an efficient tool for estimating the non-linear properties of unsaturated soils.…”
Section: Introductionmentioning
confidence: 99%
“…63,64 In recent years, machine learning and artificial intelligence techniques (hereinafter termed AI techniques) have gained popularity in geotechnical engineering applications [65][66][67] to lower costs and increase efficiency. 68,69 AI technology has been successfully applied for the estimation of the mechanical properties of saturated soils (e.g., the non-linear resilient modulus and shear strength parameters) [70][71][72][73][74] and the stability analysis of geo-structures (e.g., slopes, retaining walls, and embankments). [75][76][77] Many studies have demonstrated that AI techniques can be used as an efficient tool for estimating the non-linear properties of unsaturated soils.…”
Section: Introductionmentioning
confidence: 99%